The Ranking of Tongkat Ali Plants to Boost Testosterone Hormone Evaluated in both In vitro and In vivo Experiments - Sharifah Aminah, Tuan Said; Fatinah, Ahmad; Chakravarthi, Srikumar; Palliah, Jaya Vejayan (Faculty of Pharmacy, University of Benin, 2023)
In this study, the Tongkat Ali plants were evaluated for effect on testosterone concentrations and their order in boosting the steroidal hormone from the highest to lowest ranked. Eurycoma longifolia(EL), Stema tuberosa(ST), and Polyathia bullata(PB) are collectively referred to as “Tongkat Ali”. The roots were dried and powdered, then extracted with water under reflux. Size-exclusion chromatography was utilized to isolate the protein fraction, which was subsequently characterized using the Bradford Assay and SDS-PAGE. LC-MS was used to test for the presence of natural testosterone within the Tongkat Ali plants. For in vitroand in vivoevaluations, each plant extract was treated with TM-3 Leydig cells (50 μg/mL) for 72 hours and administered in mice (6 mg/mL) twice/day for 20 days. The extraction of EL, ST, and PB yielded 0.74%, 0.46%, and 0.34% w/w of total protein, respectively. SDS-PAGE analysis revealed a single band between 10 and 15 kDa. In vitroevaluations showed that extracts of EL, ST, and PB increased testosterone secretion by 56.02 nmol/L (41.1% compared to the untreated controls), 40.49 nmol/L (18.65%) and 36.99 nmol/L (10.93%), respectively. In the in vivostudies, EL extract showed the highest testosterone concentration at 3.85 nmol/L (51.18% compared to the untreated controls), followed by ST with 3.35 nmol/L (43.95%) and lastly, PB at only 1.88 nmol/L (9.1%). Tongkat Ali plants boosted the male hormones in both in vitroand in vivostudies, with the order being EL>ST>PB.